1951
DOI: 10.1152/ajplegacy.1951.167.3.586
|View full text |Cite
|
Sign up to set email alerts
|

An Experimental Study of Pseudopregnancy in Rat

Abstract: The APS Journal Legacy Content is the corpus of 100 years of historical scientific research from the American Physiological Society research journals. This package goes back to the first issue of each of the APS journals including the American Journal of Physiology, first published in 1898. The full text scanned images of the printed pages are easily searchable. Downloads quickly in PDF format.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

1953
1953
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 0 publications
0
12
0
Order By: Relevance
“…This finding is in general agreement with the experimental evidence reviewed by Parkes [1945], pointing to the importance of giving adrenal¬ ectomized animals salt therapy if the cessation of oestrous cycles is to be prevented. The results are at variance, however, with those of Swingle, Fedor, Barlow, Collins & Perlmutt [1951], who reported that a high proportion of adrenalectomized animals maintained on salt therapy became pseudopregnant. The authors suggest that in the rat, the removal of the adrenal glands in some way stimulates the pituitary to release sufficient LH which, in its turn, activates corpora lutea to secrete progesterone.…”
Section: Ovarian Changes After Adrenalectomy (Series I) Ovarian Weightsmentioning
confidence: 54%
“…This finding is in general agreement with the experimental evidence reviewed by Parkes [1945], pointing to the importance of giving adrenal¬ ectomized animals salt therapy if the cessation of oestrous cycles is to be prevented. The results are at variance, however, with those of Swingle, Fedor, Barlow, Collins & Perlmutt [1951], who reported that a high proportion of adrenalectomized animals maintained on salt therapy became pseudopregnant. The authors suggest that in the rat, the removal of the adrenal glands in some way stimulates the pituitary to release sufficient LH which, in its turn, activates corpora lutea to secrete progesterone.…”
Section: Ovarian Changes After Adrenalectomy (Series I) Ovarian Weightsmentioning
confidence: 54%
“…It is also interesting to note that a number of stressors are known to induce pseudopregnancy and lactational changes in the female rat (Swingle et al 1951;Nicoll et al 1961). It seems, therefore, that disruptions of reproductive function could be a non-adaptive change associated with a psychological stress response.…”
Section: Discussionmentioning
confidence: 99%
“…The release of prolactin in response to stress in the rat has been well established (Swingle, Seay, Perlmutt, Collins, Barlow & Fedor, 1951;Neill, 1970;Ajika, Kalra, Fawcett, Krulich & McCann, 1972;Dunn, Arimura & Scheving, 1972), although it is not known whether such an effect occurs in the ferret.…”
Section: Discussionmentioning
confidence: 99%